Improving Biology Learning Through Augmented Reality Technology in Indonesia: A Review - Hallaby, Syarifah Fadiya; Syahputra, Ade (Universitas Trilogi, 2024)
Biology is always considered difficult either to teach or to learn. As a field of study that learning about living subjects, biology has very broad and abstract concepts. Many students find the abstract concepts of biology are hard to understand. Some students even feel that studying biology is a dull experience. This type of perception in students subsequently led to low academic achievement. Hence, an innovative and attractive learning approach is needed for teaching biology. Augmented Reality (AR) technology has a great possibility to improve biology learning experience due to its ability to concretize the abstract concepts in biology by providing natural interaction between virtual and real-time situations simultaneously. In the last decade, numerous research of implementing AR in education including biology learning have been studied globally and nationally. In order to evaluate the effectiveness of AR in improving biology learning especially for students in Indonesia, this literature review research is conducted. The reviewed articles are retrieved through Google Scholar database with the assigned criteria published between 2020 to 2024, AR implemented, biology learning, student perception, and/or achievement in biological studies. The analysis shows that implementing AR in biology learning increases students’ interest, learning motivation, involvement, collaboration, independent learning, knowledge retention, and achievement. However, the conflicted finding is reported regarding the influence of AR on students’ critical thinking ability. Technical problems related to downloading and distributing AR applications are the main challenge that has been reported when using AR in biology learning.